THE IMAGE OF DESTINATION AS A MARKETING TOOL AND IMPACT ON THE QUALITY OF TOURISM SERVICES AN EXPLORATORY STUDY OF OPINIONS OF A SAMPLE OF TOURISTS IN RESORT OF LOWER DOKAN DAM - Suzan Ameer Kareem Al-Zahawi; Dr. Muthanna Alobaidi (Scholar Express Journals, 2023)
The study aims to demonstrate , importance image of destination(IOD) as a marketing tool independent variable that includes , its impact on quality of tourism services(IOQT) includes five dimensions represented by (reliability, responsiveness, guarantee, sympathy, tangibility) as variable accredited , standing on importance of (IOD) as a marketing tool in tourism and hospitality sector in iraq, diagnosed problem of study in weakness of cognitive , field perception , lack of information , marketing methods that are related at (IOD), the study adopted descriptive, analytical, exploratory approach used questionnaire as a main tool in collecting information, data collected data through a sample of (282) guests , visitors of the Dolan dam tourist resort were selected randomly, and a number of statistical measures and methods were used to process data. Tourist services
Keywords: destination image; as a marketing tool; quality of tourism services